Determinants of Adoption and Continuance Intention of Food Delivery Applications in Malaysia - Boon Keong Teow; Kia Hui Gan; Geegie Teh; Gordon Ho; Wen Yong Ho; Wen Cong How; Yiqing Huang; Anees Jane Ali; Daisy Mui Hung Kee (AIBPM Publisher, 2025)
In Malaysia’s competitive food delivery market, understanding factors that drive users’ continued platform use is essential. This study investigates the determinants influencing users’ continuance usage intention toward ShopeeFood in Malaysia by integrating perceived ease of use, perceived convenience, perceived usefulness, perceived value, and social influence into an extended technology acceptance model (TAM). A quantitative cross-sectional survey was conducted among 150 respondents, and data were analyzed using multiple regression via SPSS version 26. The results reveal that perceived value (? = 0.600, p 0.001) is the most influential predictor of social influence, followed by perceived usefulness (? = 0.277, p 0.01). In contrast, perceived ease of use (? = –0.245, p 0.01) shows a negative association with social influence, while perceived convenience has no significant effect. For continuance usage intention, both perceived value (? = 0.554, p 0.001) and social influence (? = 0.338, p 0.001) significantly predict ongoing usage, explaining 77% of the variance (R² = 0.770; F = 96.343, p 0.001). These findings extend the TAM by emphasizing the dominant roles of perceived value and social influence in sustaining behavioral intention, while ease of use and convenience emerge as baseline expectations in the post-adoption stage